(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Adolescents in border and coastal areas face complex psychosocial challenges, ranging from limited access to information and inadequate educational facilities to pressures in balancing local cultural values with the flow of globalization. These conditions may weaken mental resilience and hinder the development of positive character. To address this issue, a team of lecturers and students from the University of Borneo Tarakan conducted the Peer Counselor Training Based on Local Wisdom program at SMP Negeri 6 Tarakan on August 8–22, 2025. This activity was carried out under the Community Partnership Empowerment scheme with full support from the school. The implementation methods included socialization, ten training sessions, peer counseling practice, and reflection on local cultural values such as mutual cooperation, respect for parents, and care for the coastal environment. The results indicated improvements in students’ empathic communication skills, public speaking confidence, and active listening abilities. The school counselor reported a decrease in minor conflicts among students, as some problems were resolved through peer counseling. The program not only enhanced individual capacity but also strengthened collective awareness of the importance of mental resilience and character building rooted in local culture. Therefore, peer counselor training based on local wisdom has the potential to serve as a model for strengthening mental health and character education that can be replicated in other schools across border and coastal regions.